Impact of yogurt consumption on bone health markers in adults with or without osteoporosis: a systematic review and meta-analysis - Mayo, Baltasar; Malagón-Rojas, Jeadran; Agahi, Fojan; Frias, Juana; Künili, İbrahim Ender; Kütt, Mary-Liis; Mardon, Julie; Nikolovska Nedelkoska, Daniela; Parada, Mayra Alejandra; Torbica, Aleksandra; Bulmuş-Tüccar, Tuğçe; Yilmaz, Birsen; et al. (Frontiers in Nutrition, 2025)
Yogurt is a fermented dairy product widely recognized for its nutritional value and potential health benefits, particularly due to its high content of calcium, phosphorus, vitamins, and other bioactive compounds. Its purported role in promoting bone health has attracted increasing attention, especially among adults at risk of osteoporosis. However, the specific impact of yogurt consumption on bone health remains controversial, as current evidence is limited and often inconclusive. This systematic review and meta-analysis sought to evaluate the exclusive effects of yogurt consumption on bone health in adults with and without osteoporosis. Employing rigorous inclusion and exclusion criteria and standardized methodologies, the study reviewed data from both observational and clinical studies to assess the effect of yogurt consumption on bone mineral density (BMD), fracture risk, and other bone health markers. In addition, yogurt characteristics were documented in accordance with EFSA guidelines, the possible bioactive components listed, and their potential mechanism of action in relation to bone health discussed. Studies fitting the inclusion and exclusion criteria (n = 12) were all observational, limiting the ability to infer causality. The meta-analysis of cohort studies (n = 6) found no significant association between yogurt consumption and hip fracture risk (HR = 1.01, 95% CI: 0.96–1.07), while the observed positive effect on BMD was minimal and clinically irrelevant (SMD = 0.009). Although some studies reported modest improvements in BMD and bone biomarkers, the overall evidence remains inconclusive, hindered by the heterogeneity in study designs and inconsistent yogurt intake. In conclusion, current evidence does not support a significant role of yogurt consumption in preventing fractures or improving BMD in adults. Well-designed randomized controlled studies are needed to clarify its effects, particularly in adults at risk of or with osteoporosis or osteopenia. In conclusion, the effectiveness of yogurt as a primary strategy for enhancing bone health is not fully substantiated by current data, though its inclusion within a balanced diet may still offer benefits for bone health.Systematic review registrationhttps://osf.io/, 10.17605/OSF.IO/ES2PM